From Cultural Motto to Character Education: Managing the Isen Mulang Ethos of the Ngaju Dayak as Local Wisdom - Abdul Qodir; Imam Qalyubi; Abubakar Abubakar (JUMPA : Jurnal Manajemen Pendidikan, 2025)
The character formation of Indonesia's young generation faces mounting pressure as globalization outpaces the transmission of inherited moral values. Local wisdom offers a grounded alternative, yet the distinctive value systems of Kalimantan remain underused in character education. This study examines the Isen Mulang ethos of the Ngaju Dayak and reframes it from a cultural motto into a working resource for local-wisdom-based character education. A qualitative descriptive design guided the research across three regions of Central Kalimantan, namely Palangka Raya, Katingan, and Gunung Mas. Data came from 18 purposively selected informants through in-depth interviews, focus group discussions, and document analysis, and validity was secured through source, time, and technique triangulation. The findings reveal that one ethos speaks in three registers. Palangka Raya voiced a progressive spirit of hard work and forward movement, Katingan voiced social responsibility toward communal peace, and Gunung Mas voiced devotion to homeland and ancestral heritage. Read as a whole, these three value clusters form a coherent character profile that education can cultivate through planned management and transmission. The study proposes a synthesis model that moves from a single root ethos, through three regional value clusters, into an integrated character profile. Its main implication is practical. Educational managers in Central Kalimantan can draw on Isen Mulang to design character programs that help learners advance without losing the cultural identity that defines them.